Organizaciones en movimiento - Giannini, Maximiliano Luis; Lujan, Ricardo Lorenzo; Fiorani, María Fernanda; Llorente, Gonzalo; Mendez, Carla Rebeca (Estación Experimental Agropecuaria La Rioja, INTA, 2023)
EEA La Rioja